Multilocus phylogeography of a widespread savanna–woodland‐adapted rodent reveals the influence of Pleistocene geomorphology and climate change in Africa's Zambezi region. Issue 20 (12th October 2015) - McDonough, Molly M.; Šumbera, Radim; Mazoch, Vladimír; Ferguson, Adam W.; Phillips, Caleb D.; Bryja, Josef
Abstract Understanding historical influences of climate and physiographic barriers in shaping patterns of biodiversity remains limited for many regions of the world. For mammals of continental Africa, phylogeographic studies, particularly for West African lineages, implicate both geographic barriers and climate oscillations in shaping small mammal diversity. In contrast, studies for southern African species have revealed conflicting phylogenetic patterns for how mammalian lineages respond to both climate change and geologic events such as river formation, especially during the Pleistocene. However, these studies were often biased by limited geographic sampling or exclusively focused on large‐bodied taxa. We exploited the broad southern African distribution of a savanna–woodland‐adapted African rodent, Gerbilliscus leucogaster (bushveld gerbil) and generated mitochondrial, autosomal and sex chromosome data to quantify regional signatures of climatic and vicariant biogeographic phenomena. Results indicate the most recent common ancestor for all G. leucogaster lineages occurred during the early Pleistocene. We documented six divergent mitochondrial lineages that diverged 0.270–0.100 mya, each of which was geographically isolated during periods characterized by alterations to the course of the Zambezi River and its tributaries as well as regional 'megadroughts'. Results demonstrate the presence of a widespread lineage exhibiting demographic expansion 0.065–0.035 mya, a time that coincides with savanna–woodland expansion across southern Africa. A multilocus autosomal perspective revealed the influence of the Kafue River as a current barrier to gene flow and regions of secondary contact among divergent mitochondrial lineages. Our results demonstrate the importance of both climatic fluctuations and physiographic vicariance in shaping the distribution of southern African biodiversity.